Outsourcing of Hospitals Services: Lessons Learned from the Experience - Hossein Joudaki; Mahmood Heidari; Bijan Geraili (Kerman University of Medical Sciences, 2015)
Introduction: Outsourcing of hospital care was widely used after the implementation of the Third Socio-economic Development Plan in 2000 . A return in policy occurred since 2006 . Contracts between private sector and hospitals were cancelled, and the Ministry of Health employed the private sector staff. Outsourcing did not achieveits primary goals of downsizing health sector and improving efficiency. This study aimed to describe the lessons learned from the experience. Method: We conducted a qualitative study. Data were gathered by documents analysis and observations of the hospitals of medical university in Tehran and ten interviews with stakeholders and key informed persons. These people include hospital managers headquarter experts, contractors, and hospital staff. " Framework Analysis " is used to understand and analyze data. Results: We classified the factors related to unsuccessfulness of outsourcing into four categories (themes) and eight subcategories (sub-themes): 1- Factors related to employers (hospitals) including weakness in designing and monitoring contracts and hospital managers' interference with the activities of the other side of the contracts (private administration) 2- Factors related to private firms including low management knowledge and skills and pursuing short time benefits 3- Factor related to workers including workers protests 4- Factors related to policy space (upper level than hospital) including the gap between work status of formal employees and private sector workers and problems related to management. Conclusion: Unsuccessfulness of outsourcing was related to factors resulted from weak governmental hospital management system. In fact, private sector abilities and efficiency were restricted by weak hospital management potentials in public hospitals. Performing reforms in public management system is essential for successfulness of outsourcing. Keywords: Outsourcing, Private sector, Purchasing, Contracting, Hospital Citation: Joudaki H, Heidari M, Geraili B . Outsourcing of Hospitals Services: Lessons Learned from the Experience. Journal of Health Based Research 2015 1(1):13-23.